Intestinal current measurement versus nasal potential difference measurements for diagnosis of cystic fibrosis : a case-control study - Bagheri-Hanson, Azadeh; Nedwed, Sebastian; Rueckes-Nilges, Claudia; Naehrlich, Lutz; Justus Liebig University Giessen (My University, 2014)
BACKGROUND:Nasal potential difference (NPD) and intestinal current measurement (ICM) are functional CFTR tests that are used as adjunctive diagnostic tools for cystic fibrosis (CF). Smoking has a systemic negative impact on CFTR function. A diagnostic comparison between NPD and ICM and the impact of smoking on both CFTR tests has not been done. METHODS:The sweat chloride test, NPD, and ICM were performed in 18 patients with CF (sweat chloride >60mmol/l), including 6 pancreatic sufficient (PS) patients, and 13 healthy controls, including 8 smokers. The NPD CFTR response to Cl-free and isoproterenol perfusion (Delta0Cl-+Iso) was compared to the ICM CFTR response to forskolin/IBMX, carbachol, and histamine (DeltaIsc, forskolin/IBMX+ carbachol+histamine). RESULTS:The mean NPD CFTR response and ICM CFTR response between patients with CF and healthy controls was significantly different (p <0.001), but not between patients with CF who were PS and those who were pancreatic insufficient (PI). Smokers have a decreased CFTR response measured by NPD (p=0.049). For ICM there is a trend towards decreased CFTR response (NS). Three healthy control smokers had NPD responses within the CF-range. In contrast to NPD, there was no overlap of the ICM response between patients with CF and controls. CONCLUSIONS:ICM is superior to NPD in distinguishing between patients with CF who have a sweat chloride>60mmol/l and healthy controls, including smokers. Neither NPD nor ICM differentiated between patients with CF who were PS from those who were PI. Smoking has a negative impact on CFTR function in healthy controls measured by NPD and challenges the diagnostic interpretation of NPD, but not ICM.
Keywords: cystic fibrosis; nasal potential difference; intestinal current measurement; sweat chloride; sweat test; ddc:610